Metastasis of Gastric Signet-Ring Cell Carcinoma to the Urinary Bladder: A Case Report and Review of the Literature - Kerem Okutur; Orhan Onder Eren; Gokhan Demir (Case Reports in Oncological Medicine)
Although signet-ring cell (SRC) adenocarcinoma is commonly seen in the stomach, it is a very rarely seen histologic entity in the bladder. It is difficult to distinguish primary SRC adenocarcinoma of the bladder from bladder metastasis of SRC carcinoma of the stomach only based on histological findings. In such cases, clinical findings and immunohistochemical studies may be helpful. We present here a 48-year-old male patient presenting with hematuria and abdominal pain. Computerised tomography of the patient revealed a gastric mass, peritoneal involvement, and thickening of the bladder wall, and histopathological analysis revealed SRC adenocarcinoma in both of the endoscopic biopsies taken from the stomach and bladder. Immunohistochemical analyses confirmed the diagnosis of SRC adenocarcinoma of the bladder secondary to gastric cancer.